Reverse cardiac remodeling in patients undergoing combination therapy of transcatheter mitral valve repair - Yokoyama, Hiroaki; Ruf, Tobias Friedrich; Geyer, Martin; Tamm, Alexander R.; Da Rocha E Silva, Jaqueline Grace; Gößler, Theresa Ann Maria; Zirbs, Julia; Schwidtal, Ben; Münzel, Thomas; von Bardeleben, Ralph Stephan (Frontiers in Cardiovascular Medicine, 2023)
Aims For patients with severe mitral valve regurgitation (MR), different kinds of transcatheter mitral valve repair (TMVr) exist, targeting the leaflets, annulus, and chordae. The concomitant combination (COMBO) therapy of TMVrs is rarely used as treatment, and there are very few publications about this therapeutic strategy. We evaluated the effect of COMBO-TMVr on the cardiac left chambers and clinical data, including survival. Methods We included 35 patients at high risk who underwent concomitant sequential transcatheter mitral valve edge-to-edge repair (M-TEER) and another TMVr for severe MR in our hospital between March 2015 and April 2018. Of these, 13 had adequate follow-up transthoracic echocardiography (TTE) up to around 1 year after the procedure. Results Survival for all patients was 83% at 1 year, 71% at 2 years, and 63% at 3 years, respectively. In the 13 patients with adequate TTE follow-up, M-TEER plus either Cardioband (n = 4), Carillon Mitral Contour System (n = 7), or Neochord (n = 2) were used, respectively. Ten patients had secondary, and three patients primary MR. After 1 year, changes [median (Q1, Q3)] of left ventricular (LV) end-systolic diameter of −9.9 cm (−11.1, 0.4), LV end-diastolic diameter of −3.3 cm (−8.5, 0.0), LV end-systolic volume (LVESV) of −17.4 mL (−32.6, −0.4), LV end-diastolic volume (LVEDV) of −13.5 mL (−15.9, −3.2), LV mass of −19.5 g (−24.2, −7.6), and left atrial volume (LAV) index (LAVi) of −16.4 mL (−23.3, −11.3) were observed. A significant reduction was also seen in the change ratios of LVESV, LVEDV, LV mass, and LAVi, respectively. Conclusion We found that COMBO therapy of TMVr seems feasible and may support reverse remodeling of left cardiac chambers during 1 year after the procedure in a cohort of patients at high risk.